Bihar Third Five Year Plan Progress Report for the Period Ending June, 1962 - Planning Commission (Planning Commission, 1962)
Statement Showing the Progress of Plan Expenditure Under Major heads of Department During the Quarter Ending June, 1902, Statement Showing the Progress of Plan Expenditure During the Quarter Ending June, 1962, Irrigation, Power, Panchayat. Co-Operation, Community Development and Gram Panchayat.
Bihar